2009
DOI: 10.1111/j.1467-6486.2009.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Firm Experience and Market Entry by Venture Capital Firms (1962–2004)

Abstract: In this paper, we examine a firm's decision to enter new markets as related to the depth and breadth of its experience and the relative distance of those markets. We situate our discussion and analysis in the context of the venture capital (VC) industry, and examine whether and when US VC firms enter five high-technology investment markets through first- or later-round investments. This setting allows us to observe both the firms that chose to enter a new market and those that did not, and analyse the antecede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 84 publications
1
45
0
Order By: Relevance
“…We measure the extensiveness of a VC firm's experience by the total number of rounds of investment that the firm has made prior to a given year. This measure has been used in prior studies to measure the operating experience of organizations that lead to experiential learning (Dimov and Martin de Holan, ; Ingram and Baum, ; Tuschke et al, ) and is thus most appropriate for our purposes.…”
Section: Data Method and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We measure the extensiveness of a VC firm's experience by the total number of rounds of investment that the firm has made prior to a given year. This measure has been used in prior studies to measure the operating experience of organizations that lead to experiential learning (Dimov and Martin de Holan, ; Ingram and Baum, ; Tuschke et al, ) and is thus most appropriate for our purposes.…”
Section: Data Method and Modelmentioning
confidence: 99%
“…This characteristic makes them more prone to enter new markets compared to inexperienced firms (King and Tucci, ). In the VC industry, Dimov and Martin de Holan () likewise found that experience predisposes VC firms to enter new investment markets.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…When making new investments, VC firms face choices between staying in the existing markets and entering new markets (Dimov & Martin de Holan, 2010), that is, investing in companies that operate in the industries in which the VC firms had not invested previously. VC firms confront greater uncertainty about the ultimate nature of technology and customers' needs in the market's initial stages when they enter into an emerging industry.…”
Section: Choices Of Governance Modes That Determine Early Entrymentioning
confidence: 99%
“…Our dependent variable is the exploratory learning of VC firms, which was measured by a dummy variable indicating whether a VC firm entered a new industry in which it had never invested before in year t + 1. Prior research has used a VC firm's entry into a new industry to indicate firm exploration (Dimov and Martin de Holan, 2010). As discussed by Dimov and Martin de Holan (2010), firm exploration can be only understood as newness or search for new ideas in relation to a focal firm's specific activities or domains.…”
Section: Sample and Datamentioning
confidence: 99%